Biosynthesis of morin-3-O-rhamnopyranoside in a genetically engineered Escherichia coli - Thuần, Nguyễn Huy; Trung, Nguyễn Thành; Quyền, Đồng Văn; Hằng, Vũ Thị Thu; Sohng, Jae Kyung (Vietnam Journal of Biotechnology, 2018)
Flavonoids are significant secondary metabolites of vascular plants. They have been proven to possess numerous types of anti-bacterial, anti-tumor, anti-oxidant and anti-inflammatory bioactivities etc. Thereby, there are many flavonoids extracted and purified from plants and have been used for biological tests. Nevertheless, the traditional extraction methods require a large amount of initial sample, tedious and professional techniques and low yield of target compound. Until present, the advanced development of genetic engineerings and recombinant protein as platform allow synthesis of high amount of different types of flavoid in short time. Escherichia coli is one of the most popular host for whole-cell biotransformation of flavonoids and their derivatives due to its simple genetical, physiological system and fast growth. In this paper, we described the biosynthetic method of morin-3-O-rhamnopyranoside from a genetically engineered E. coli using morin as substrate. In particular, the E. coli harboring biosynthetic gene cluster of activated TDP-L-rhamnose and gene encoding for glycosyltransferase was used as host for biotransformation. Morin was fed into the culture broth of recombinant E. coli for rhamnosylation. The formation of morin-3-O-rhamnopyranoside was then quantitied and qualified using Thin Layer Chromatography (TLC), Reverse Phase High Performance Liquid Chromatography (RP-HPLC) and Liquid Chromatography Electrospray Ionization Tandem Mass Spectrometric (LC-ESI-MS/MS) assays. The highest yield of product (56.5 µM) was achieved after 48h, 32 oC and pH = 7.2-8.0. This result showed that morin-3-O-rhamnopyranoside was succesfully synthesized in the genetically engineered E. coli. Furthermore, metabolic engineering of intra-cellular system for improving absorption of substrate as well as excretion of product or enhancement of glycosyltransferase activity may increase the final yield of biotransformation process